The Allergen Bureau VITAL Program. (23rd November 2019) - Taylor, Simon Brooke; Christensen, Georgina; Grinter, Kirsten; Sherlock, Robin; Warren, Lisa
Abstract: This paper sets out the role of the Allergen Bureau and the Voluntary Incidental Trace Allergen Labelling (VITAL) Program from its origin in 2007 to its current iteration, VITAL 2. Herewith are outlined the scientific principles that support the program; the program's application in the food chain; and the benefits of the program's use to the food industry, clinicians, and the allergic consumer. VITAL was developed by the Australian and New Zealand food industry in consultation with multiple stakeholders, including consumer organizations, industry bodies, regulators, and retailers, to provide a standardized, science-based risk assessment process for the investigation of the potential presence of food allergens due to cross-contact and to determine whether, for cases in which the allergen is unable to be removed or controlled consistently, precautionary statements are required. The aim of the program is to provide a consistent process, a standardized approach, and a relevant cross-contact statement to allow the allergic consumer to make an informed decision regarding consumption of food.